EFL students’ long-term practice of Data-driven Learning (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2021)
Data-driven Learning (DDL) has been widely used in language classrooms and suggested to promote learner autonomy and retention. The current study would confirm if the findings of research in other countries are also found in Indonesian context within different time span. Therefore, this study investigates Indonesian EFL students’ long-term practice of DDL after one semester has passed since they learned with DDL using corpus data. The participants of this study were university students specializing in English Language Education and the setting of this study was at one public university in Central Kalimantan Province of Indonesia where English is a foreign language. Survey research with one-shot design was conducted and questionnaire comprising of three dimensions (learners’ retention of learning materials and current knowledge of DDL, current practice of DDL, and future plan) was distributed to collect data. The results show positive trends that the students had retention of the learning materials they learned in the previous semester through DDL, they currently employed DDL independently outside classrooms, and they would apply DDL in the future.
Keywords: Data-driven Learning; EFL students; corpora